Implementasi Natural Language Processing (NLP) pada Layanan Pengelolaan Surat Kantor Camat Bukit Barisan - Rahmadani, Suci (Universitas Negeri Padang, 2024)
The application of Natural Language Processing in letter processing services aims to implement writing error detection or text processing in this system, apart from that it is also designed to be able to classify documents automatically according to their type. This system was built using the Python programming language with the Flask framework which is supported in the form of an NLP library. NLP is a branch of Artificial Intelligence that focuses on natural language processing. In designing and building this system using UML modeling. The development method used in this system is a prototype, several stages in this method, namely the first Listen to Customer (Listening to Customers/Clients), the second Build and Revise Mock-up (Build and Improve Prototype) and the last Customer Test Drives Mockup (Testing). Key Words: NLP;Text Processing; Document Classification;Letter Processing Services;Prototype.